STUDI IKONOGRAFI ORNAMEN PADA INTERIOR MASJID AGUNG AL FATTAH MOJOKERTO - Hariyanto, Vernanda Juni; Badriyah, Siti (Institut Seni Indonesia Surakarta, 2022)
The Great Mosque of Al Fattah is a mosque built in 1877 which was the first Muslim worship building in Mojokerto City. This research uses qualitative research methods based on Panofsky's Iconography theory. The research was conducted through three stages, namely pre-iconography, iconographic analysis, and iconography interpretation. The results showed that the ornaments on the Great Mosque of Al Fattah have a stylistic meaning that is in accordance with the interior style, namely Majapahit-Middle East, but there are some ornaments whose use is not appropriate to the interior style of Majapahit- Middle East.